Collective marketing: Making maize a profitable product in Tanzania - Karamuna, Wilson (Technical Centre for Agricultural and Rural Cooperation, 2018)
The Producer Empowerment and Market Linkages (PEML) project is improving the livelihoods of local maize producer groups in Tanzania by strengthening their organisational and operational capacities. The project is also facilitating farmer group access to market information systems and financial services, as well as promoting their participation in warehouse receipt systems.